THE PHENOMENON OF THE LEADERSHIP OF THE WORLD COUNTRIES IN THE MARKET HIGH TECHNOLOGIES - RIBCHUK, A.; ZHURBA, IGOR (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In today’s globalized world, the level of technological development and innovation of the state is one of the main indicators of its competitiveness in the international arena. The country’s participation in the exchange of high technologies determines its success in world trade, as well as the profitability of national companies. For the state as a whole, knowledge-intensive technologies are a determining factor of economic development, the main source of replenishment of budget funds and a fundamental basis for ensuring its national security. Undoubtedly, international trade in high technologies is the most important factor in the country’s involvement in integration processes. Currently, a significant role in this process is played by innovation structures - various technology parks, innovation clusters, whose activities are aimed at developing and implementing new technologies. The latter become an important impetus for further globalization of world economic relations. The creation of a high-tech product and the corresponding integration of a state into the world market of high technologies determines its place and role in the modern system of international economic relations. The article examines the preconditions and current trends of the phenomenon of technological leadership of developed countries, which is explained by the massive redistribution of resources in the production chains of the new technological way with the simultaneous spread of relevant social and institutional innovations. The reasons for China’s technological breakthrough, which are due to financial assistance from the state through the creation of various funds to stimulate the development of high technology, are analyzed. It can exercise its leadership only in cooperation with existing global players in the high-tech market in conditions of open competition. The consequences of technological leadership of the USA, Germany, France and other leading countries in the market of high-tech products are revealed. State strategies for the development of high technologies support not only individual technologies, but also aimed at solving environmental problems, effective health care, increasing the mobility of factors of production. The potential economic effect of the introduction of new technologies by all actors in the world economy is shown.